2016
DOI: 10.1299/jbse.15-00613
|View full text |Cite
|
Sign up to set email alerts
|

Severity of cyclist head injuries caused by impacts with vehicle structure and road surface

Abstract: For cyclist fatalities in 2014 in Japan, the head was the most frequently injured body region. In the present study, the authors analyzed the features of cyclist head injuries in real-world traffic accidents using the data of patients who were taken to the emergency room in Dokkyo Medical University Koshigaya Hospital in Japan, from 2011 to 2013. The results indicated that the percentage of skull fractures was the highest among cyclist head injuries. Assuming that a helmet can prevent head injuries sustained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…In particular, the reduction in the peak skull strain used to estimate the skull fracture (92%-97%) was much larger than that for other head injuries. A study reported that skull fracture (25%) was the most frequent head injury, followed by subarachnoid bleeding (16%), and subdural hematoma (12%) in cyclists involved in traffic accidents (Oikawa et al, 2016b). Bambach et al (2013) indicated that head injury risk reduction was significantly associated with helmet use, with a reduction up to 74% overall, including a 78% reduction in skull fracture, 72% reduction in intracranial injury, 74% reduction in concussive injury, and 80% reduction in open head wounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, the reduction in the peak skull strain used to estimate the skull fracture (92%-97%) was much larger than that for other head injuries. A study reported that skull fracture (25%) was the most frequent head injury, followed by subarachnoid bleeding (16%), and subdural hematoma (12%) in cyclists involved in traffic accidents (Oikawa et al, 2016b). Bambach et al (2013) indicated that head injury risk reduction was significantly associated with helmet use, with a reduction up to 74% overall, including a 78% reduction in skull fracture, 72% reduction in intracranial injury, 74% reduction in concussive injury, and 80% reduction in open head wounds.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pedestrian head protection performance tests for vehicle hoods have been evaluated by the HIC (Matsui, 2011). When Oikawa et al (2016b) conducted impact experiments against the A-pillar of a vehicle and a road using a headform impactor with and without a helmet, the helmeted cases resulted in a 60% HIC reduction for impacts against a vehicle and an 86% HIC reduction for impacts against the road. Considering the results obtained from this study, those reductions would correlate with skull fractures, not brain injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficient of friction between the head or helmet and the wall was set to 0.5, as was the friction coefficient between the head and helmet (Fahlstedt et al, 2016). The FE bicycle helmet model was validated by comparison with a drop experiment of the helmet against the pavement (Oikawa et al, 2016). The comparison yielded good agreement between the resultant accelerations in the simulation and the experiment.…”
Section: Simulation Using An Fe Model Of the Human Head And An Fe Bicmentioning
confidence: 99%